Perancangan Ulang User Interface Aplikasi ERP Berdasarkan User Experience Menggunakan Design Thinking - Wijaya, Husaini; Pibriana, Desi (Universitas Multi Data Palembang, 2025)
The design of an effective User Interface (UI) is a key factor in supporting the implementation of an Enterprise Resource Planning (ERP) system. PT Duta Abadi Primantara is one of the companies that use ERP in its operational activities. However, users have reported complaints regarding complex navigation, inappropriate color selection, and the absence of error notifications. Therefore, this study aims to redesign the user interface of the ERP application using the Design Thinking method. The Design Thinking method consists of five stages: Empathize, Define, Ideate, Prototype, and Test. In this study, data were collected through interviews, observations, and the distribution of the User Experience Questionnaire (UEQ). The design prototype was created using Figma and tested through UEQ analysis to assess improvements in user experience. The test results showed significant improvements in attractiveness, efficiency, clarity, accuracy, and stimulation, while the novelty aspect did not experience a significant increase. Based on the UEQ testing results, the redesigned UI of the ERP application provides a better user experience, making navigation more intuitive and optimizing the application's visual appearance to enhance user productivity.